Hubungan Antara Stres Menyelesaikan Skripsi Dengan Prokrastinasi Akademik Pada Mahasiswa - Mutya, Mita Fani Tri; Monica, Cintiya; Muliati, Riska; Rahmi, Rahmi (Batanang : Jurnal Psikologi, 2023)
Stress experienced by students in completing the thesis can lead to negative behavior reactions in itself related to thesis such as avoiding thesis work, doing other activities that are considered interesting and procrastination or procrastination. The purpose of this study is to determine the relationship of stress completing thesis with academic procrastination in students. Sampling technique in this research using probability sampling technique with saturated sampling method. The sample in this study amounted to 70 students or students who are completing the thesis in the Faculty of Psychology UIR. Method of data retrieval used in this research by using Likert scale. The scale used is the scale of stress completing the thesis and the scale of academic procrastination. The reliability coefficient of the stress scale completes the thesis of 0.893 and the academic procrastination scale of 0.902. Statistical analysis used in this research product moment correlation, through the help of SPSS program version 22.0 for windows. These statistical results have shown that there is a significant positive correlation between stress completing thesis to academic procrastination of (r = 0,333 ', p = 0,005). Effective contribution of stress variable completing thesis with academic procrastination is 11,1%, so hypothesis accepted because there is positive relation between two variables that is, the higher the stress of finishing thesis the higher the academic procrastination, otherwise the lower the stress of finishing thesis the lower the academic procrastination.┬áKeywords: ┬áAcademic Procrastination, Stress, Student